Negative effect of vitamin D on kidney function: a Mendelian randomization study. Issue 12 (30th April 2018) - Teumer, Alexander; Gambaro, Giovanni; Corre, Tanguy; Bochud, Murielle; Vollenweider, Peter; Guessous, Idris; Kleber, Marcus E; Delgado, Graciela E; Pilz, Stefan; März, Winfried; Barnes, Catriona L K; Joshi, Peter K; et al.
ABSTRACT: Background: The kidney plays a central role in the regulation of vitamin D metabolism. It is not clear, however, whether vitamin D influences kidney function. Previous studies have reported conflicting results, which may have been influenced by reverse causation and residual confounding. We conducted a Mendelian randomization (MR) study to obtain unconfounded estimates of the association between genetically instrumented vitamin D metabolites and estimated glomerular filtration rate (eGFR) as well as the urinary albumin:creatinine ratio (UACR). Methods: We performed a two-sample MR study based on three single nucleotide variants associated with 25(OH)D levels: rs2282679, rs10741657 and rs12785878, related to the genes GC, CYP2R1 and DHCR7, respectively. Estimates of the allele-dependent effects on serum 25(OH)D and eGFR/UACR were obtained from summary statistics of published genome-wide association meta-analyses. Additionally, we performed a one-sample MR analysis for both 25(OH)D and 1, 25(OH)2 D using individual-level data from six cohorts. Results: The combined MR estimate supported a negative causal effect of log transformed 25(OH)D on log transformed eGFR ( β = −0.013, P = 0.003). The analysis of individual-level data confirmed the main findings and also revealed a significant association of 1, 25(OH)2 D on eGFR ( β = −0.094, P = 0.008). These results show that a 10% increase in serum 25(OH)D levels causes a 0.3% decrease in eGFR. There was no effect of 25(OH)D on UACR ( β = 0.032, P = 0.265). Conclusion: Our study suggests that circulating vitamin D metabolite levels are negatively associated with eGFR. Further studies are needed to elucidate the underlying mechanisms.